Development of community mental health services: the case of Emilia‑Romagna italian region - Fioritti, A (2009)
Italian psychiatry has gained International attention after its radical reform of 1978, which established the progressive closure of mental hospitals and the establishment of community services throughout the country. However it is technically inappropriate to talk about Italian psychiatry as the devolution process has transferred to the regions all competences about policy, planning and evaluating health services. This explains the variety of “community psychiatries” that can be found along the peninsula and the reasons of interest that can arise from their comparison. The development of community psychiatry in Emilia‑Romagna, a region of 4 million inhabitants in Northern Italy, has proceeded through two partially overlapping phases of deinstitutionalization (1978‑1997) and development of integrated mental health departments (1990‑2008). The analysis of raw data about allocation of resources and professional capital development give way to tentative comparisons with the current Portuguese situation of implementation of a similar reform. In 2006 the regional Council launched a three year project aimed at rethinking the welfare system and the integration of social and health services, considering the dramatic social and demographic changes occurring in the region. This project has implied also a three year process of redrafting mental health policy finalised in the Emilia‑Romagna Mental Health Action Plan 2009‑2011 approved by the council in March 2009. It basically follows two strategies: integration of health and social services and further qualification of health services. The former is pursued through a reshaping of the planning and commissioning bodies of both health and social services, previously separated and now merging. They are taking responsibility on many issues related to mental health care, such as prevention, mental health promotion, supported employment, supported housing, subsidies, self‑help. The improvement of community services is an objective to be achieved through formal accreditation and quality assurance mechanisms and through a widespread system of participation of users and carers to all levels of planning and monitoring.